Essential Oils as Antimicrobials in Crop Protection - María Alonso-Gato; Gonzalo Astray; Juan C. Mejuto; Jesus Simal-Gandara (MDPI AG, 2021)
At present, organic crops have reached an important boom in a society increasingly interested in the conservation of the environment and sustainability. It is evident that a part of the population in the Western world focuses their concern on how to obtain our food and on doing it in a way that is as respectful as possible with the environment. In this review, we present a compilation of the work carried out with the use of essential oils as an alternative in the fight against different bacteria and fungi that attack crops and related products. Given the collected works, the efficacy of essential oils for their use as pesticides for agricultural use is evident.